PENGEMBANGAN MODUL AJAR DAN LKPD BERBASIS PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS II SEKOLAH DASAR MATERI PENJUMLAHAN - Dani Anisa Imanda; Syafri Ahmad; Salmaini Salmaini (STKIP Subang, 2025)
This study aims to develop and evaluate a Problem Based Learning (PBL)-based teaching module and student worksheet (LKPD) to improve second-grade students’ understanding of addition without regrouping. The study is motivated by conceptual difficulties often faced by lower-grade students, who tend to memorize procedures without understanding the relationships among numerical values, concrete representations, and symbolic forms. This research employed a Research and Development (R&D) approach using a simplified Plomp model through preliminary research, development, and evaluation stages. The learning design refers to Arends’ five-phase PBL syntax: problem orientation, organizing learning, guiding inquiry, developing and presenting results, and evaluating the problem-solving process. The findings show that the implementation reached a 96% completion rate in PBL syntax, categorized as “very good.” Student engagement reached 92%, demonstrated through group discussions, manipulation of concrete objects, and presentations. In the individual evaluation, 23 out of 25 students (92%) achieved mastery, while two required remedial support due to errors in counting tens. Additionally, 88% of students successfully transitioned from concrete representation to symbolic notation. Challenges encountered included classroom noise, uneven participation among several students, and limited investigation time; however, these were resolved through simplified teacher instructions and structured guidance. Overall, the PBL-based module and LKPD proved practical, effective, and feasible, and show potential for wider implementation in early-grade mathematics learning to enhance conceptual understanding and collaborative skills.